Judging Whether it is Aesthetic: Does Equilibrium Compensate for the Lack of Symmetry?. (1st January 2013) - Samuel, Françoise; Kerzel, Dirk
In two experiments, we explored whether compositions made up of two or three rectangles received high aesthetics ratings when the composition was equilibrated, that is, when the center of mass of the weights represented by the areas of the rectangles were in the center of the composition. We supposed that equilibrated stimuli might be appreciated as much as symmetric stimuli. We further wanted to find out whether aesthetics ratings, balance ratings, and weight ratings differ from each other, and which stimulus characteristics influence each rating. We observed that the position of the center of mass of the compositions influenced the aesthetics ratings only slightly whereas it influenced the weight ratings more strongly. In contrast with this, the variation of the overall shape of the rectangles making up the compositions influenced the aesthetics ratings more strongly than the weight ratings. At first sight, balance ratings appeared intermediate between the aesthetics ratings and the weight ratings. However, when we varied the area ratio of the rectangles making up the composition, we observed that the balance ratings were independent of the two other ratings.